Smoking-Related Disciplinary Violations as Maladaptive Coping among Cadets in a High-Discipline Boarding School - Cica Selfiana Ismelda; Mimbar Oktaviana (Journal of Educational, Health and Community Psychology, 2026)
This study explored smoking-related disciplinary violations as maladaptive coping responses among cadets experiencing psychological pressure within a high-discipline boarding school environment at the Surabaya Merchant Marine Polytechnic. Smoking violations among cadets are commonly interpreted as intentional noncompliance with institutional rules; however, limited qualitative attention has been given to the psychological mechanisms underlying such behavior in semi-military educational settings. This study employed a qualitative multiple-case study design involving ten male cadets selected through purposive sampling. Data were collected through semi-structured interviews, non-participant observation, and documentation review, and analyzed using thematic analysis. The findings identified six interrelated themes: boarding school educational pressure, smoking as maladaptive coping, peer influence, emotional suppression, family support, and adaptive potential. Smoking behavior was primarily described as a temporary emotion-focused coping response to boredom, stress, loneliness, emotional tension, and accumulated psychological pressure rather than deliberate resistance toward institutional authority. Emotional suppression and peer normalization increased vulnerability to maladaptive coping, whereas family support, exercise, prayer, advice-seeking, and future-oriented motivation functioned as protective factors supporting adaptive adjustment. This study contributes to the literature by reframing smoking-related disciplinary violations as psychologically mediated coping responses rather than merely disciplinary misconduct. The findings highlight the importance of integrating disciplinary systems with psychological support, emotional regulation interventions, and adaptive coping development within boarding school institutions.